2014
DOI: 10.1093/jnci/djt378
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib in Advanced, Chemoresistant Anaplastic Lymphoma Kinase–Positive Lymphoma Patients

Abstract: Anaplastic lymphoma kinase (ALK)-positive lymphomas respond to chemotherapy, but relapses, which bear a poor prognosis, occur. Crizotinib inhibits ALK in vitro and in vivo and was administered as monotherapy to 11 ALK+ lymphoma patients who were resistant/refractory to cytotoxic therapy. The overall response rate was 10 of 11 (90.9%; 95% confidence interval [CI] = 58.7% to 99.8%). Disease status at the latest follow-up is as follows: four patients are in complete response (CR) (months >21, >30, >35, >40) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 19 publications
3
163
1
Order By: Relevance
“…Housekeeping genes used for normalization were murine HPRT FW: 5 0 -TCAGTCAACGGGGGACATAAA-3 0 ; REV: 5 0 -GGGGC-TGTACTGCTTAACCAG-3 0 or human GAPDH FW: 5 0 -Tgcaccaccacctgcttagc-3 0 ; REV: 5 0 -GGCATGGACTGTGGTCATGAG-3 0 . Deep sequencing was performed as previously described (20).…”
Section: Pcr Quantitative Rt-pcr and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Housekeeping genes used for normalization were murine HPRT FW: 5 0 -TCAGTCAACGGGGGACATAAA-3 0 ; REV: 5 0 -GGGGC-TGTACTGCTTAACCAG-3 0 or human GAPDH FW: 5 0 -Tgcaccaccacctgcttagc-3 0 ; REV: 5 0 -GGCATGGACTGTGGTCATGAG-3 0 . Deep sequencing was performed as previously described (20).…”
Section: Pcr Quantitative Rt-pcr and Sequencingmentioning
confidence: 99%
“…Very limited data are available on ALCL patients (19). The first long-term follow-up of ALCL patients who received Crizotinib reported, after 2 years, a PFS of 63.7% and an OS of 72.7%, and the drug was in general well tolerated (20). However, despite great success, as expected from previous experience with tyrosine kinase inhibitors (TKI; refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…207 Gambacorti-Passerini et al reported nine adult patients with refractory ALK-positive ALCL treated with crizotinib. 201 All patients obtained response, and, at the time of the report, four of the patients were on crizotinib and in CR without stem cell transplantation (duration of response: > 21, > 30, > 35, and > 40 months). The estimated 2-year PFS and OS rates were 63.7% and 72.7%, respectively.…”
Section: Alk Inhibitorsmentioning
confidence: 92%
“…[200][201][202][203][204][205][206] In a pediatric phase I trial evaluating crizotinib for refractory solid tumors or ALCL, seven of nine (78%) patients with ALK-positive ALCL achieved CR. 207 Gambacorti-Passerini et al reported nine adult patients with refractory ALK-positive ALCL treated with crizotinib.…”
Section: Alk Inhibitorsmentioning
confidence: 99%